2015
DOI: 10.1128/jcm.02026-14
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Signature of Multidrug-Resistant Salmonella enterica Serovar Typhi Isolates Related to a Massive Outbreak in Zambia between 2010 and 2012

Abstract: dRetrospectively, we investigated the epidemiology of a massive Salmonella enterica serovar Typhi outbreak in Zambia during 2010 to 2012. Ninety-four isolates were susceptibility tested by MIC determinations. Whole-genome sequence typing (WGST) of 33 isolates and bioinformatic analysis identified the multilocus sequence type (MLST), haplotype, plasmid replicon, antimicrobial resistance genes, and genetic relatedness by single nucleotide polymorphism (SNP) analysis and genomic deletions. The outbreak affected 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 50 publications
10
78
1
Order By: Relevance
“…This outbreak investigation revealed that CFR was 1% which is in line with investigations in Zambia (Hendriksen et al, 2015) which indicates early detection of the outbreak and management of cases. Typhoid fever suspected cases were higher in females than males.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This outbreak investigation revealed that CFR was 1% which is in line with investigations in Zambia (Hendriksen et al, 2015) which indicates early detection of the outbreak and management of cases. Typhoid fever suspected cases were higher in females than males.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, there was the higher likelihood of spreading the disease if appropriate hygiene practices were poorly observed and also exposure through household activities including preparation of food. However, it is in contrast with a study done in Zambia (Hendriksen et al, 2015).…”
Section: Discussioncontrasting
confidence: 74%
“…In one study over five Asian countries the incidence ranged from 15 to 450/100,000 population/year [69]. The burden in Africa has been more difficult to determine as estimates, based on a handful of studies may have overestimated the number of cases [70]. Indeed in the 2010 study [8] advises caution in interpreting its estimates as one Kenyan study contributes disproportionately [10].…”
Section: Enteric Fevermentioning
confidence: 99%
“…Since the 1990s, alternative treatment options have included fluoroquinolones, third-generation cephalosporins (such as ceftriaxone) and the azalide azithromycin 1 . The early emergence of MDR S. Typhi was driven in large part by the acquisition of IncHI1 plasmids carrying antibiotic resistance genes 12 and, more recently, by chromosomal mutations associated with resistance to fluoroquinolones, and MDR strains have been reported across Asia and Africa 1316 .…”
mentioning
confidence: 99%